PENGARUH PEMBELAJARAN BERBASIS WEB DENGAN GOOGLE SITES TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V - Cicha Veronika Purba; Anton Sitepu; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article is derived from research about the effect of web-based learning with Google Sites on Mathematics learning outcomes for students at class V of SD RK. Budi Luhur in Medan Denai in the academic year 2020/2021. The approach used in the research was a quantitative approach. The sampling technique used Simple Random Sampling based on the population of 56 students. The researchers took a sample from 36 students in the experimental class. The results indicated that students’ learning outcomes by using web-based learning with Google Sites were in the very good category with an average of 85.27. Testing for normality obtained a significance value of 0.200. If 0.200 > 0.05, hence, data of class V were normally distributed. In the correlation test, the correlation coefficient was 0.873 with a significance of 0.05, which meant rcount (0.873) > rtable (0.329). Thus, there was a positive correlation between web-based learning with Google Sites and mathematics learning outcomes of fifth-grade students. The results of the t-test test were 10.426 > 2.032, which means Ha was accepted. It shows that there was a positive and significant effect of web-based learning with Google Sites on students’ learning outcomes.